2008
DOI: 10.1186/1471-2164-9-543
|View full text |Cite
|
Sign up to set email alerts
|

Genomic characterization of putative allergen genes in peach/almond and their synteny with apple

Abstract: Background: Fruits from several species of the Rosaceae family are reported to cause allergic reactions in certain populations. The allergens identified belong to mainly four protein families: pathogenesis related 10 proteins, thaumatin-like proteins, lipid transfer proteins and profilins. These families of putative allergen genes in apple (Mal d 1 to 4) have been mapped on linkage maps and subsequent genetic study on allelic diversity and hypoallergenic traits has been carried out recently. In peach (Prunus p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 38 publications
2
70
0
2
Order By: Relevance
“…Amongst the 12 putative genes we mapped, the two allergic genes, LTP1(or putative allergen Pru du 3.01) and Pru1 (prunin1), have been mapped in Prunus maps previously (Viruel et al 1995;Joobeur et al 1998;Chen et al 2008). The reported locations on linkage groups 6 and 8, respectively, are conWrmed by our mapping results.…”
Section: Discussionsupporting
confidence: 85%
“…Amongst the 12 putative genes we mapped, the two allergic genes, LTP1(or putative allergen Pru du 3.01) and Pru1 (prunin1), have been mapped in Prunus maps previously (Viruel et al 1995;Joobeur et al 1998;Chen et al 2008). The reported locations on linkage groups 6 and 8, respectively, are conWrmed by our mapping results.…”
Section: Discussionsupporting
confidence: 85%
“…Recent data indicated that a Pru p 1.01 isoform, named Pru p 1.06D according to its sequence identity (Gao et al, 2005;Chen et al, 2008), is one of the most abundantly expressed genes among the ripe peach mesocarp transcriptome (Trainotti et al, 2006). Pru p 1.06D shows high sequence identity (73%) to Pru p Figure 5.…”
Section: Discussionmentioning
confidence: 99%
“…Other sequences within the same cluster include apple Md-PR5 and pear Ppy-TLP with sequence similarities of 91 and 92%, respectively. Pp-TLP3 is probably a homolog of Pru p 2.04 (99% similarity), the putative allergene from (P. dulcis 9 P. persica) (Chen et al 2008). Pp-TLP3 is located within the same cluster of Brassica rapa (Br-TLP).…”
Section: Characterization Of Peach Pr1 and Tlp Proteinsmentioning
confidence: 99%
“…8). Regardless of many putative elements identified in the PlantPAN database (Chen et al 2008), only those with a previously demonstrated role in disease resistance or hormone signaling were considered. The binding sites for transcription factors MYC2 (JA signaling), ERF (JA/ET signalling), WRKY (SA signalling) and TGA (SA signaling) were recognized in both plus and minus DNA-strands.…”
Section: The Identification Of Cis-acting Elements In Tlp Promotersmentioning
confidence: 99%